Determination of the main technological parameters of cyclic-steam stimulation of oil reservoirs with account of heat losses along the borehole - Gilmanov, Alexander Yanovich; Kovalchuk, Tatyana Nikolayevna; Shevelev, Alexander Pavlovich (Computational Continuum Mechanics, 2023)
Due to the decline in light oil reserves, the development of high-viscosity oil fields has become more relevant today. One of the most common methods of thermal enhanced oil recovery is cyclic-steam stimulation. Compared to other techniques, this method has an advantage of providing higher thermal efficiency due to selection of its parameters with account of variations in the basic properties of a heat carrier as it moves towards the well bottom. The purpose of this work is to create a method for rapid assessment of optimal technological parameters of cyclic-steam stimulation, in which the temperature distributions along boreholes obtained from geophysical research are used as initial data. The created method allows determination of the time of hot carrier injection, steam soak and oil production. The scientific novelty of the study refers to the fact that an integrated approach relating the problem of hot carrier transportation with the problem of determination of optimal parameters for reservoir treatment is proposed for the first time. The cyclic-steam stimulation process is described by the equations of mechanics of multiphase systems. Euler’s method is used to solve the resulting system of equations. The paper presents: functions of depth-wise distributions of pressure, temperature and velocity and dryness fraction of steam; temperature distribution in the multilayer wall of the well and in the rock (considering a specified heat transfer between the layers of the well materials, water and rock at known temperatures); optimal values of the time of hot carrier injection, steam soak and oil production. The calculations have shown that, due to the in the layer of basalt fiber, the temperature in the multilayer wall of the well decreases within 80%. The maximum value of additional cumulative oil recovery has been established by analyzing the calculated bottom-hole parameters of the heat carrier.